STEM on Science Learning in Indonesia: An Opportunity and A Challenge - Muhammad Reyza Arief Taqwa; Abd Aziz Ardiansyah; Muhammad Agni Nurhidayat (Indonesian Journal Of Educational Research and Review, 2020)
STEM has become a strategic issue in learning on an international scale, as well as in Indonesia. Related to the term "STEM" in Indonesia, it is often referred to as an approach to learning. This research is a literature study that examines four things, namely, the introduction of STEM, which is an integration of four disciplines (Science, Technology, Engineering, and Mathematics) in learning; Approaches that can be used in STEM implementation are The SILO Approach, The Embedded Approach, and The Integrated Approach; STEM opportunities in science learning in Indonesia can improve concept understanding, problem-solving skills, scientific literacy skills, creative thinking skills, and critical thinking skills; and the challenge when implementing STEM in learning is the demand for teachers to be able to understand the relationship between disciplines in STEM and demands in the technological aspects that all schools in Indonesia cannot meet.